Theological Meaning of the Paintings of Matskhvarishi Archangel’s Church - Ketevan Gongadze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
This article discusses the fresco paintings of Zemo Svaneti Latali Matskvarishi Church of the Archangels and their ideological-theological designation. In these paintings the iconography of the scenes of the Christological cycle, their compositional structure are noticeably complicated. The subjects are not arranged in either historical or chronological order and various iconographic schemes are employed. Concepts of the Resurrection and Sacrifice, which are presented in the sanctuary and the western wall decor, are further developed on the walls of the church. The scenes placed in different registers echo each other ideologically and make up the image of Christ’s glory in the arch. Specific sections present the scenes that are unified within a theological concept, related to each other in a semantic way that clearly shows deep theological thoughts distinguished by including different scenarios: annunciation, revelation, victim, resurrection and salvation of conceptual accents are distributed on the wall- arch. Announcement concerning the embodiment of the Lord, his wordly eminence (“Annunciation,” “Nativity”), manifestation of the divine nature of Christ Redeemer (“Candlemas,” “Transfiguration,” “The raising of Lazarus”, “Descent of the Holy Spirit,” “Dormition of the Mother of God”), sacrifice offered by him (“The crucifixion”), resurrection – arrival with glory, (“Resurrection” , “Christ of Old Days”) The above-mentioned ensemble of paintings is associated with the salvation of the soul and the concept of the resurrection.